Interaction of xylitol with whey proteins: Multi-spectroscopic techniques and docking studies. (1st October 2020) - Kong, Fanhua; Kang, Shimo; Tian, Jinlong; Li, Mohan; Liang, Xiaona; Yang, Mei; Zheng, Yan; Pi, YuZhen; Cao, XueYan; Liu, YiMing; Yue, Xiqing
Highlights: Xylitol (XY) interacts to whey proteins (WPIs) contributed to tryptophan quenching. XY has the highest binding susceptibility to α-La among WPI fractions. Hydrogen bonding, Van der Waals forces, and hydrophobic forces are the main forces involved in the interaction. WPIs conformation dramatically changed in association with XY. The interaction results in changes in functionality of WPI. Abstract: This study aimed to examine the interaction mechanism between xylitol (XY) and whey protein isolate (WPI) using multispectral techniques and molecular docking. Additionally, we investigated the effect of XY on WPI functionality using the method of fluorescent probe, high-speed dispersion and differential scanning calorimetry. The fluorescence quenching results such as quenching constants, binding constants and thermodynamic parameters showed strong susceptibility to interacting of WPI and its fractions to XY and the sequence was: α-lactalbumin (α-La) > bovine serum albumin (BSA) > β-lactoglobulin (β-Lg). Docking results revealed that XY was bound to the residues of aromatic cluster II in α-La, the hydrophobic cavity of β-Lg and the subdomain IIA of BSA through hydrogen bonding and van der Waals forces, resulting in conformational changes in secondary structures of proteins, which converted α-helix to β-turn and random coils. Further, XY increased thermal stability and emulsifying properties and reduced surface hydrophobicity and zeta-potential of WPI.